Amantadine and/or transcranial magnetic stimulation for fatigue associated with multiple sclerosis (FETEM): study protocol for a phase 3 randomised, double-blind, cross-over, controlled clinical trial - Antonio Portoles; Julián Benito-León; Jordi A Matias-Guiu; Jorge Matias-Guiu; Julio Prieto; Javier González-Rosa; Miguel Ángel Hernández; Maria Luisa Martínez-Ginés; Natalia Pérez-Macías; Iván Padrón (BMJ Open)
Introduction Fatigue is one of the most disabling symptoms of multiple sclerosis (MS), and effective treatments are lacking. Amantadine is one of the most used treatments, although its efficacy is under debate. Transcranial magnetic stimulation (TMS) is a promising intervention that has shown positive effects in some preliminary investigations. We aim to investigate the effect of 6 weeks of amantadine and/or TMS in fatigue due to MS.Methods and analysis The study is a national, multicentre, phase 3, randomised, double-blind, cross-over, placebo-controlled and sham-controlled clinical trial. Adult patients with relapsing-remitting MS, Expanded Disability Status Scale score of 1.5–4.5 and Fatigue Severity Score>4 are eligible for the trial. Participants will be randomised to one of the sequences of the study. Each sequence consists of four periods of 6 weeks of treatment and three washout periods of 12–18 weeks. All patients will receive all the combinations of therapies. The primary outcome is the Modified Fatigue Impact Scale. The secondary outcomes are the Symbol Digit Modalities Test (cognition), Beck Depression Inventory-II (depressive symptoms) and Short-Survey 12 (quality of life). Safety and cost-effectiveness will also be evaluated. An exploratory substudy including MRI and blood biomarkers will be conducted.Ethics and dissemination The study is approved by the Ethics Committee of the Hospital Clinico San Carlos and the Spanish Agency of Medications and Medical Devices. All study findings will be published in scientific peer-reviewed journals and presented at relevant scientific conferences.Trial registration number EudraCT 2021-004868-95; NCT05809414.